Qumran, early Judaism, and New Testament interpretation Kleine Schriften III - Frey, Jörg (Wissenschaftliche Untersuchungen zum Neuen Testament ;, 2019)
Back cover: How did the Qumran discoveries change New Testament scholarship? What are the main insights to be gained from the Qumran corpus with regard to the Jesus tradition, Paul's language and theology, the dualistic language and worldview of the Fourth Gospel, or the formation of the biblical Canon? The articles of this volume present the fruits of 25 years of scholarship on Qumran and the New Testament.